"Alexa… what pills do I need to take today?". Issue 6 (26th June 2020) - Beaney, Paul; Kalirai, Hardip Singh; Chambers, Ruth
Abstract : Can personal digital assistants such as Amazon Alexa help to improve patients' adherence to their medicines? Here, the authors discuss the potential and the limitations of this technology, and describe their pilot study in patients with diabetes and other underlying health conditions.